EFFECTIVENESS AND TOLERABILITY OF BISOPROLOL/PERINDOPRIL SINGLE-PILL COMBINATION IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE AND CONCOMITANT HYPERTENSION WHO HAD A HISTORY OF MIOCARDIAL INFARCTION. (June 2022) - Burtsev, Yuriy; Boytsov, Sergey; Karpov, Yuriy; Khomitskaya, Yunona
Abstract : Objective: To evaluate effectiveness and tolerability of bisoprolol/perindopril single-pill combination (Bis/Per SPC) in the subgroup with stable coronary artery disease (CAD) and concomitant hypertension (HTN) and a history of myocardial infarction (MI) Design and method: STYLE (NCT03730116) was a 3-month, multicenter, open-label, uncontrolled observational study conducted in Russia. Stable CAD patients (n = 1892) comorbid with HTN and treated with Bis/Per SPC were included from November 2018 to January 2019. Data were collected at 3 visits: V1 (inclusion visit), V2, V3 (1, 3 months). In this post-hoc analysis, the antihypertensive effectiveness of Bis/ Per SPC in the subgroup with a history of MI was assessed by mean change in systolic (SBP) and diastolic blood pressure (DBP) and antianginal effectiveness - by mean changes in number of angina attacks and short acting nitrates (SAN) intake. Treatment tolerability was assessed by investigators as excellent, good, or acceptable. Results: Subanalisis included 495 patients (26.2%) with a history of MI. At baseline (BL), mean age was 62.9 ± 8.5 years, 39.0% (n = 193) were women, mean SBP and DBP were 155.5 ± 16.2 mmHg and 92.1 ± 10.3 mmHg, respectively and mean heart rate (HR) was 80.2 ± 10.3 bpm. By V3, mean SBP/DBP significantly decreased by 29.6 ± 15.2/15.5 ± 10.0 mmHg respectively (p < 0.0001 for both) and 86.9% (n = 430) of patients achieved target BP < 140/90 mmHg. Mean HR decreased by 12.1 ± 8.5 bpm after 1 month and by 16.1 ± 9.6 bpm after 3 months (p < 0.0001 for both) and 27.3% (n = 135) of patients reached target level of HR (55–60 bpm). The proportion of patients who achieved target BP (<140/90 mmHg) with HR < 60 bpm at V3 was 27, 5 % (131 of 476). The number of angina attacks per week and intake of SAN decreased from 5.2 ± 14.5 and 5.0 ± 4.9 (at V1) to 0.8 ± 1.7 and 1.3 ± 1.7 (at V3), respectively (p < 0.0001 for both). 97% of investigators rated tolerability of SPC as excellent or good at V3. Conclusions: In stable CAD patients with HTN and a history of MI treated with Bis/Per SPC for 3 months, significant improvement in BP and HR control, reduced angina attacks and SAN intake were observed, and treatment was well tolerated.